2006
DOI: 10.1007/s10750-006-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fish in Structuring Invertebrates on Stromatolites in Cuatro Ciénegas, México

Abstract: Stromatolites, the dominant Precambrian life form, declined in the Phanerozoic to occur today in only a few sites. This decline has been attributed to evolution of metazoan grazers, but stromatolites in our study site, Cuatro Cie´negas, Coahuila, Me´xico, harbor diverse macroinvertebrates. Drawing on food chain theory, we hypothesized that fish predation on invertebrates controls invertebrate populations, allowing stromatolites to flourish in Cuatro Cie´negas. Our experiment used small mesh (1 mm) cages to exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…2c). The micro-habitat characteristics of extant microbialites may, thereby, be providing localized respite for invertebrates from predation (Dinger et al 2006;Konishi et al 2001) and harsh physical conditions, as well as offering an oxygen refuge (Des Marais 2003;Gingras et al 2011;Herman and Kump 2005;Mobberley et al 2015). For example, in the South African stromatolite pools during the warmer months, anoxic events have been observed whereby a milky benthic layer with a distinctive hydrogen sulphide odor forms [oxygen concentrations as low as 0.24 mg L −1 , compared to supersaturated levels of up to 37.0 mg L −1 above the stromatolites (Perissinotto et al 2014;Rishworth et al 2016)], from which metazoans might use the adjacent stromatolite matrix as a temporary oxygen refuge during daylight hours.…”
Section: Resultsmentioning
confidence: 99%
“…2c). The micro-habitat characteristics of extant microbialites may, thereby, be providing localized respite for invertebrates from predation (Dinger et al 2006;Konishi et al 2001) and harsh physical conditions, as well as offering an oxygen refuge (Des Marais 2003;Gingras et al 2011;Herman and Kump 2005;Mobberley et al 2015). For example, in the South African stromatolite pools during the warmer months, anoxic events have been observed whereby a milky benthic layer with a distinctive hydrogen sulphide odor forms [oxygen concentrations as low as 0.24 mg L −1 , compared to supersaturated levels of up to 37.0 mg L −1 above the stromatolites (Perissinotto et al 2014;Rishworth et al 2016)], from which metazoans might use the adjacent stromatolite matrix as a temporary oxygen refuge during daylight hours.…”
Section: Resultsmentioning
confidence: 99%
“…Other springs are located at the base of alluvial fans (Wolaver and Diehl, 2011). CO 2 -rich spring water with pCO 2 1.5-3 orders of magnitude higher than atmosphere facilitates deposition of rare modern freshwater stromatolites (Dinger et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The size and types of bioherms vary from the large, complex forms and depth distributions observed in the larger and much deeper Lake Tanganyika to smaller forms in other basins such Laguna Chichancanab and Cuarto Cienegas in Mexico. The biologically built structures that occur in isolated desert springs of Cuarto Cienegas (Winsborough & Golubić, 1987;Dinger et al, 2006) have similar high concentrations of calcium sulfate to those observed in Chichancanab. These reef-like formations can dry out during low lake levels and then reform once the water levels rise; wave action can move them during storms and rounded forms sometimes form in shallow waters (Covich, personal observations).…”
Section: Environmental Complexity and Constraints On Population Dynamicsmentioning
confidence: 75%
“…In Chichancanab, crayfish excavate and hollow out the concretions and use them for refuge. Habitat structure influences how different predatory species search for food and defend feeding territories in the shallow littoral zones of lakes (e.g., Stevenson, 1992;Dinger et al, 2006;Horstkotte & Plath, 2008;Plath & Strecker, 2008).…”
Section: Environmental Complexity and Constraints On Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation